Moyamoya Disease, a Rare Cause of Recurrent Strokes in an African Sickle Cell Child: Does hydroxyurea have a Role in this Context? - Makubi, Abel; Soka, D.; Makani, J. (International Journal of Child Health and Nutrition, 2012)
Background: Neurological complications are a significant cause of morbidity and mortality in sickle cell patients with reported incidence of stroke in Africa as high as 1·3/100 patient per year [1,2]. There is an association between sickle cell disease (as well as other hemoglobinopathies) and Moyamoya disease [3]. Data on the occurrence of this condition in African sickle patient are scare. Likewise the role of hydroxyurea among patients with both sickle cell anemia and Moyamoya disease in preventing stroke has not yet been studied in Africa. Case presentation: In the present report, we describe an African child who had a recurrent stroke. She was later diagnosed as having Moyamoya disease while already receiving hydroxyurea. Conclusion: Moyamoya disease is a rare condition associated with recurrent stroke in African sickle children. The role of hydroxyurea in this context is still unclear.